2022
DOI: 10.3389/fpls.2022.1032243
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Brazilian barley breeding: Changes in developmental phases and ecophysiological traits

Abstract: Despite recognizing the importance of genetic improvement in the production of barley grains, little information is available on the contribution of phenological development to the genetic improvement of Brazilian barley. Field experiments were carried out between 2011 to 2013, in the absence of biotic and abiotic stresses and with preventive lodging control. Five two-rowed spring barley cultivars, released between 1968 and 2008, were evaluated. Although there was no significant association in the cycle length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Additionally, the cytokinin-degrading enzyme HvCKX3 is directly regulated by HvMADS1 to integrate temperature response and cytokinin homeostasis, which are necessary to inhibit meristem cell cycle/division [137]. Moreover, barley production was improved by changing the modern barley leaf architecture to have a greater vertical inclination (electrophilic canopy) so that photosynthetically active radiation could enter the crop canopy [138]. Other research showed that in order to maximize yield production in challenging environmental conditions, proper timing of plant development is essential, and the use of wild barley genes could boost grain yield formation.…”
Section: Barleymentioning
confidence: 99%
“…Additionally, the cytokinin-degrading enzyme HvCKX3 is directly regulated by HvMADS1 to integrate temperature response and cytokinin homeostasis, which are necessary to inhibit meristem cell cycle/division [137]. Moreover, barley production was improved by changing the modern barley leaf architecture to have a greater vertical inclination (electrophilic canopy) so that photosynthetically active radiation could enter the crop canopy [138]. Other research showed that in order to maximize yield production in challenging environmental conditions, proper timing of plant development is essential, and the use of wild barley genes could boost grain yield formation.…”
Section: Barleymentioning
confidence: 99%